Molecular methods for detection of prognostic and predictive markers in diagnosis of adenoid cystic carcinoma of the salivary gland origin - Šteiner, Petr; Pavelka, Jaroslav; Vaneček, Tomáš; Miesbauerová, Markéta; Skálová, Alena (Ceskoslovenska patologie, 2018)
Adenoid cystic carcinoma of salivary gland origin (AdCC) is second most common salivary carcinoma characterized by frequent recurrences, perineural invasion and high long-term mortality rate. The surgical resection of the tumor in combination with adjuvant radiotherapy is the only method of choice. AdCC has been studied, altogether with immunohistochemistry, by numerous molecular-genetic techniques. Some of them, e.g. reverse-transcription PCR or fluorescent in situ hybridization contributed to the identification of translocation t(6;9)(q22-23;p23-24), which results in fusion of two transcription factors MYB-NFIB. For AdCC is this fusion unique among salivary gland carcinomas and serves as a diagnostical tool in differential diagnosis of histopathologically difficult cases. More complex methods, such as next-generation sequencing helped to detect other molecular level changes; and hence improved understanding of a development, behavior and pathogenesis of this possibly fatal malignancy. This review summarizes basic knowledge of AdCC on the genome, transcriptome and epigenetic level, which were achieved using molecular-genetic and immunohistochemical methods. Keywords: adenoid cystic carcinoma - salivary carcinoma - MYB-NFIB - FISH - aCGH - NGS.
Keywords: Biomarkers, Tumor; Neoplasm Recurrence, Local; adenoidně cystický karcinom; nádorové biomarkery; Salivary Gland Neoplasms; Salivary Glands; lokální recidiva nádoru; Humans; lidé; hybridizace in situ fluorescenční; Carcinoma, Adenoid Cystic; Prognosis; prognóza; slinné žlázy; nádory slinných žláz; In Situ Hybridization, Fluorescence